INDEPENDENSI KEKUASAAN KEHAKIMAN DARI PENGARUH KEKUASAAN DI INDONESIA - M. Syahrul Borman (Lex Journal: Kajian Hukum & Keadilan, 2017)
The freedom of Judges based on the independence of Judicial Power in Indonesia is guaranteed in the Constitution of Indonesia, namely the 1945 Constitution, which is further implemented in the Law on Judicial Power. Thus, the judicial power must be free and impartial, it will only be realized if it is subject to the rules of law in force. If the judicial power does not maintain the proper distance from the political institutions that exist within a country, then it will lose its legitimacy, and its presence in a country becomes meaningless.